Kisspeptin and Metabolism: The Brain and Beyond - Dudek, Monika; Ziarniak, Kamil; Sliwowska, Joanna H. (Frontiers in Endocrinology, 2018)
Apart from the well-established role of kisspeptin (Kp) in the regulation of reproductive functions, recent data described its action in the control of metabolism. Of particular interest for the review is the population of Kp neurons localized in the arcuate nucleus (ARC) of the hypothalamus, the site of the brain where reproductive and metabolic cross-talk occurs. However, within the hypothalamus Kp does not work alone, but rather interacts with other neuropeptides, e.g. neurokinin B, dynorphin A, proopiomelanocortin, the cocaine and amphetamine regulated transcript, agouti-related peptide and neuropeptide Y. Beyond the brain, Kp is expressed in peripheral tissues involved in metabolic functions. In the review we will mainly focus on the local action of this peptide in peripheral organs such as the pancreas, liver and the adipose tissue. We will concentrate on dysregulation of the Kp system in cases of metabolic imbalance, e.g. obesity and diabetes. Importantly, these patients besides metabolic health problems often suffer from disruptions of the reproductive system, manifested by abnormalities in menstrual cycles, premature child birth, miscarriages in women, decreased testosterone levels and spermatogenesis in men, hypogonadism, and infertility. We will review the evidence from animal models and clinical data indicating that Kp could serve as a promising agent with clinical applications in regulation of reproductive problems in individuals with obesity and diabetes. Finally, emerging data indicate a role of Kp in regulation of insulin secretion, potentially leading to development of further therapeutic uses of this peptide to treat metabolic problems in patients with these lifestyle diseases.